Effects of anticoagulant therapy on pregnancy outcomes in patients with thrombophilia and previous poor obstetric history. Issue 3 (April 2015) - Mutlu, Ilknur; Mutlu, Mehmet Firat; Biri, Aydan; Bulut, Berk; Erdem, Mehmet; Erdem, Ahmet
Abstract : This study investigates the effects of anticoagulant therapy on pregnancy outcomes in 204 patients with thrombophilia and previous poor obstetric outcomes. Patients with poor obstetric history (pre-eclampsia, intrauterine growth retardation, fetal death, placental abruption, recurrent pregnancy loss) and having hereditary thrombophilia were included in this study. Poor obstetric outcomes were observed more frequently in patients who had not taken anticogulant therapy compared with treated group. Live birth rate, gestational age at birth and Apgar scores were significantly higher in the treated group when compared with the untreated group. There were no significant differences in terms of birthweight, mode of delivery and admission rates to the neonatal intensive care unit (NICU). Low-molecular-weight heparin (LMWH) plus acetylsalicylic acid (ASA) had higher gestational age at birth, Apgar scores, live birth rate and a lower abortion rates when compared with controls; in contrast, no significant difference was observed in terms of birthweight, mode of delivery, obstetric complications and admission rates to NICU. There were no significant differences between control group and both LMWH only and ASA only groups in terms of gestational age at birth, Apgar scores, birthweight, mode of delivery, obstetric complications and admission rates to NICU. Only LMWH group had higher live birth rate as compared with control group. The use of only ASA did not seem to affect the perinatal complication rates and outcomes. In conclusion, anticoagulant therapy with both LMWH and ASA seems to provide better obstetric outcomes in pregnant women with thrombophilia and previous poor obstetric outcomes.